Compendium of biomedical instrumentation - Khandpur, Raghbir Singh, 1942- (Hoboken, NJ : Wiley, 2019)
"Accelerometers are widely used as sensors for wearable medical devices to measure and assess physical activity in clinical/laboratory settings or free-living environments. They are, however, mostly employed for ambulatory monitoring for continuously measuring long-term activities of subjects in a free-living environment. From the recorded activity data , it is possible to identify daily movements which are associated with an individual's functional status. It is also possible to detect adverse activity , such as falls through signal analysis and appropriate algorithm. In addition, energy expenditure is the most commonly found application of the accelerometers"--
Includes index.
Keywords: Medical instruments and apparatus -- Encyclopedias